SURFACE ELECTROELASTIC SHEAR WAVES IN A SYSTEM OF PIEZOACTIVE LAYER AND HALF-SPACE - Belubekyan, V. M.; Belubekyan, M. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
A piezoactive half-space with a piezoactive layer on its surface is considered. Materials of the layer and the half-space are piezoelectrics of class 6 mm with different properties. Shear stresses between the two piezoelectrics are taken to be zero. Interaction between shear waves in the layer and the half-space is due to continuity of electrical field on their surface. Existence condition of the surface waves is obtained. It is established, that two waves of Gulayev-Bleustain type can exist in considered system